Impact modeling of foam cored sandwich plates with ductile or brittle faceplates - Sridhar, Idapalapati (2013)
This paper reports numerical results of low velocity impact on open-face sandwich plates with an impactor of 2.65 kg mass hitting with 6.7 m/s velocity. The numerical simulation is done using 3D finite element models in LS-DYNA. The sandwich plates used for the present work have a core made of commercial aluminum alloy foam (Alporas) with faceplates made of either ductile aluminum (Al) or brittle carbon fiber reinforced plastic (CFRP). Selection of suitable constitutive models and erosion criterion for the failure analysis is investigated. A simplified analytical model for the peak load prediction under punch-through failure mode is presented. Numerically predicted contact force versus time, energy absorbed versus time along with the failure modes are compared with the experimental measurements and observations. Within experimental scatter, there is a good agreement between the numerical predictions and experimental measurements. Further more, the analytically predicted peak load values are in excellent agreement with the experimental measurements.